2018
DOI: 10.1097/spv.0000000000000472
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative Outcomes, Complications, and Efficacy of Robotic-Assisted Prolapse Repair: A Single Institution Study of 196 Patients

Abstract: In this large series of robotic prolapse repair, complications are infrequent. Short-term apical outcomes are excellent. Few women required additional compartment repairs within 1 year with 6% rate of mesh exposure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 18 publications
2
10
0
Order By: Relevance
“…There have been several studies assessing results after robotic sacrocolpopexy. 10,13,14 Gupta and colleagues showed only two apical recurrences in 196 women undergoing robotic prolapse repair, with a mean follow-up time of 9 months. 13 Other studies, too, have shown improvement in QOL scores using the PFDI and the PFIQ.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There have been several studies assessing results after robotic sacrocolpopexy. 10,13,14 Gupta and colleagues showed only two apical recurrences in 196 women undergoing robotic prolapse repair, with a mean follow-up time of 9 months. 13 Other studies, too, have shown improvement in QOL scores using the PFDI and the PFIQ.…”
Section: Discussionmentioning
confidence: 99%
“…10,13,14 Gupta and colleagues showed only two apical recurrences in 196 women undergoing robotic prolapse repair, with a mean follow-up time of 9 months. 13 Other studies, too, have shown improvement in QOL scores using the PFDI and the PFIQ. 1418 In a recently published study by Jong and colleagues, following robotic mesh sacrocolpopexy of 56 women with a mean follow-up time of 3 years, mean AUA QOL score improved significantly from a mean of 4–1.78 postoperatively.…”
Section: Discussionmentioning
confidence: 99%
“…One retrospective review of over 450 minimally-invasive sacrocolpopexies reported a prolapse recurrence rate of ~11% with no difference between robotic versus laparoscopic routes of surgery (30). A second retrospective case series of 195 RSC identified a 7% prolapse recurrence rate, with a retreatment rate of less than 5% (29). Similarly, in systematic reviews, whether restricting to randomized trials or including nonrandomized comparative trials, the outcomes between LSC and RSC are high and do not differ significantly (23,24).…”
Section: Robotic Sacrocolpopexymentioning
confidence: 99%
“…However, adverse outcomes such as high rate of the Gram staining and post-culture failure to isolate the agent, or high false-negative rate in bacteriological and histological tests may be encountered (11,12). The systemic symptoms, such as fever, fatigue are rare, but the pain is often observed in this disease, and it has also sneaky and silent clinical course.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, to make a definite etiologic diagnosis; CT-guided percutaneous needle biopsy, open biopsy may be carried out, and in the cases, where the fistula from the epidural area to the skin tissue, associated with abscess formation is also observed, a definitive diagnosis may be made by identifying the causative microorganisms in culture antibiograms made from wound site swabs (10,11).…”
Section: Introductionmentioning
confidence: 99%